Penerangan Jalan Umum Tenaga Surya: Studi Kasus di Kota Pangkalpinang - Febrianto, Andika; Sunanda, Wahri; Gusa, Rika Favoria (Universitas Diponegoro, 2019)
This research was conducted to design public street lighting photovoltaic, based on SNI 7391:2008 concerning specifications of public street lighting in urban areas with several parameters that were considered by poles, lights used, intensity of light needed, number of lights needed and supporting equipment for public street lighting photovoltaic. Currently, Jenderal Sudirman road in the city of Pangkalpinang along 1.5 km uses electricity from PLN with 30 units of 150 watt SON lamps and 11 lux light intensity. The design obtained for street lighting photovoltaic while still meet SNI for light intensity, obtained supporting equipment for solar street lighting, namely 31 unit of 8 meter octagonal poles with specifications of 40 watt LED lights for each cross arm, 1 unit of 100 Wp solar panels, unit of 100 Ah VRLA batteries and 1 unit of solar charger controller (10A, 12V / 24V).